TAX BEHAVIOR AND EARNINGS BEHAVIOR OF CORPORATE MANAGERS: CASE OF BANKS AND DECENTRALIZED FINANCIAL SYSTEMS IN BENIN (Journal of Business Management and Accounting, 2025)
This research looks at the influence of tax behavior on the earnings behavior of corporate managers in Republic of Benin, a West African country. The author uses the generalized method of moments (GMM) on dynamic panel data. The sample consists of 21 firms, i.e. 11 banks for the period 2011 to 2020 and 10 DFSs for the period 2016 to 2021. It turns out that earnings behavior is influenced more positively by corporate income tax (CIT), then by tax savings due to debt interest deduction (EIDID); and negatively by interest on debt (INTEREST), by dividends (DIVIDEND) and by past earnings before interest and tax (EBIT(-1)). This paper is one of the first to extend the literature by identifying the main determinants of earnings behavior, notably the positive effect of corporate income tax (CIT).